Slave Trade from Usora: Dubrovnik’s Intermediary Role in the Medieval Social Context - Duranović, Elmedina (Historical Thought, 2025)
The medieval slave trade involving individuals from the region of Usora constituted a significant facet of broader economic and social currents in the Adriatic and beyond. Drawing on published archival sources from Dubrovnik, alongside relevant domestic and international scholarship, this article examines the mechanisms and trajectories of slave trade originating in Usora. Particular attention is given to young women, whose roles extended beyond domestic and artisanal labour to include sexual exploitation, often in the form of concubinage. By foregrounding the gendered dimensions of slavery and positioning Dubrovnik as a pivotal intermediary in the late medieval human trafficking network, the study also seeks to advance historical inquiry into Usora and Soli - regions of strategic importance that remain underexplored in current historiography.